Arquivistas: uma análise sob o viés da sociologia das profissões - Mintegui, Evelin Melo (2014)
This study sought to understand the profession of archivist's point of view of the sociology of professions. From a literature review on the topic of the professions, the concept of field of Pierre Bourdieu was critical to design the research object. So, looking up the field of archival science and profession, postings were collected on social networks from archivists in relation to his profession, as well as interviews with some individuals were performed. The documentary survey was also necessary to characterize the profession and its history in the country (Brazil). During the data analysis it was found that there was no possibility of designing the archival field, since this concept requires a certain independence. Once considered the field of information science, we chose the contemporary informative documentary field as a reference to locate archivistics (archival science) and the profession of archivist, competing with other areas of knowledge and professions which also take the files as its objects (historians, librarians). The analysis revealed strategies to strengthen both the knowledge area as the profession.